Gold Mining in Boh River (2007-2021) - Nurhayati Sudang; Muhamad Sopyan; Sainal A. (Yupa: Historical Studies Journal, 2026)
This article examines the emergence and development of gold mining in Boh River, Mahakam Ulu Regency, from 2007 to 2021. Using the historical method through heuristics, source criticism, interpretation, and historiography, the study draws on interviews, field observation, and secondary materials such as books, legal documents, journals, and archival or documentary sources available to the author. The findings show that gold mining in Boh River emerged from the convergence of alluvial resource potential, limited local employment, community livelihood strategies, and collective mining practices. Its development was marked by a gradual shift from panning with a dulang to machine-assisted extraction using pumps, compressors, and river transport. This technological change reshaped labor relations among miners, workers, capital owners, and gold collectors. Although mining activities faced legal uncertainty and occupational risk, they persisted because they offered a more immediate source of income than other rural livelihoods. The article contributes to local economic history by showing how small-scale mining transformed work, mobility, and social status in an upriver Kalimantan community.